An Insider's Guide to the UN - Fasulo, Linda M. (New Haven : Yale University Press, 2015)
"Termed "the indispensable source on the United Nations" by Joseph S. Nye of Harvard's Kennedy School of Government, this book is now fully revised and updated to include new material on fragile states, R2P (responsibility to protect), recent Security Council issues such as the revolts in Libya and Syria, and a greatly expanded section on understanding and participating in a Model UN. "This easily readable overview of the main activities of the United Nations system provides the reader with an appreciation of its complexity and of its many programs and agencies."-James S. Sutterlin, author of The United Nations and the Maintenance of International Security; Distinguished Fellow in UN Studies, Yale University "With highly readable and journalistic clarity, the author leads readers through the complex organizational structure of the United Nations. Her concise and entertaining narrative sheds light on its mission, evolution, and controversies."-Jackie Gropman and Susan Woodcock, School Library Journal"--
Includes bibliographical references and index.
Keywords: United Nations -- Popular works; POLITICAL SCIENCE / Peace